2015
DOI: 10.1159/000368807
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Degree of Endoscopic Atrophy of the Gastric Mucosa and Carcinogenic Risk

Abstract: Background: The relationship between Helicobacter pylori infection and gastric cancer has been demonstrated, and the risk of gastric cancer occurrence is known to increase with the progression of atrophic changes associated with chronic gastritis. Endoscopic evaluation of the degree and extent of atrophy of the gastric mucosa is a simple and very important means of identifying a group at high risk for gastric cancer. This study aimed to clarify the carcinogenic risk in relation to the degree of atrophy. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
82
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 25 publications
(26 reference statements)
2
82
0
1
Order By: Relevance
“…The percentage changes in the PG I/II ratio are useful as indices for distinguishing outcome in eradication therapy for H. pylori [36]. In Japan, recently, the combination of serum PG level and H. pylori -IgG level, namely, the ABC method, has been commonly used at health screenings as a useful marker of gastric cancer [37]. However, because of their elevated levels, it was considered difficult to use serum PG as a biomarker of gastric atrophy and gastric cancer, gastric acid secretion level, or determinant of outcome in eradication therapy in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage changes in the PG I/II ratio are useful as indices for distinguishing outcome in eradication therapy for H. pylori [36]. In Japan, recently, the combination of serum PG level and H. pylori -IgG level, namely, the ABC method, has been commonly used at health screenings as a useful marker of gastric cancer [37]. However, because of their elevated levels, it was considered difficult to use serum PG as a biomarker of gastric atrophy and gastric cancer, gastric acid secretion level, or determinant of outcome in eradication therapy in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, detection of chronic H. pylori infection is thought to be important for predicting the risk of gastric cancer [32][33][34][35]. For endoscopic observation, atrophic gastritis is established as the most typical and frequent appearance of gastric mucosa with H. pylori infection [22,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…For endoscopic observation, atrophic gastritis is established as the most typical and frequent appearance of gastric mucosa with H. pylori infection [22,35,36]. Therefore, a strong association between ''UGI-ESbased'' and ''UGI-XR-based'' diagnoses suggests that detection of UGI-XR-based atrophic gastritis can lead to evaluation of chronic H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, eradication therapy does not prevent the development of metachronous gastric cancer completely [29]. Moreover, the risk of gastric cancer rises with the progress of atrophy [30] [31] [32], and Kato et al [33] showed that gastric atrophy could develop in Japanese children of an average age of 12 years with H. pylori infection. In addition, we have shown significant over expression of several years old (57.9%) comparing to the elder group of more than 50 years old (35.1%) [40].…”
Section: Discussionmentioning
confidence: 99%